Analisis Pengaruh Financial Distress, Pertumbuhan Perusahaan Dan Ukuran Perusahaan Terhadap Auditor Switching - Indah Puspitasari; Ida Ayu Nursanty; M. Wahyullah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This research aims to examine the influence of financial distress, company growth and company size on auditor switching. The research variables consist of 3 (three) independent variables, namely financial distress (X1), company growth (X2) and company size (X3) as well as the dependent variable, namely auditor switching (Y). This study uses secondary data obtained from financial statements and independent auditors' reports published via the internet through the official website of the Indonesia Stock Exchange www.idx.co.id (IDX). The sample in this research is coal mining companies listed on the Indonesia Stock Exchange 2018-2022. Sampling using purposive sampling, 8 companies were obtained. The analytical method used is multiple linear regression analysis. The results showed that financial distress (X1), company growth (X2) and company size (X3) had a significant effect on auditor switching (Y), with a significant level of 79.1%. Meanwhile, the remaining 20.9% of auditor switching is influenced by other variables outside the independent variables in this research.